2022
DOI: 10.1021/acs.orglett.1c04241
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical-Oxidation-Promoted Direct N-ortho-Selective Difluoromethylation of Heterocyclic N-Oxides

Abstract: An efficient and green electrochemical N-ortho-selective difluoromethylation method of various quinoline and isoquinoline N-oxides has been developed. In this method, sodium difluoromethanesulfinate (HCF2SO2Na) was used as the source of the difluoromethyl moiety, and various N-ortho-selective difluoromethylation quinoline and isoquinoline N-oxides were obtained in good to excellent yields under a constant current. In addition, the reaction was easy to scale up and maintained a good yield. Preliminary mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Similarly, the Zhang and Fang group recently reported the use of sodium difluoromethanesulfinate for the electrochemically induced difluoromethylation of quinoline and isoquinoline N-oxides. [134]…”
Section: Electrochemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the Zhang and Fang group recently reported the use of sodium difluoromethanesulfinate for the electrochemically induced difluoromethylation of quinoline and isoquinoline N-oxides. [134]…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…However, difluoromethylation and trifluoroethylation reactions were effective only for the most reactive substrates whereas trifluoromethylation was much more efficient in general, as it will be discussed later in this review article, which reflects the poorer reactivity of the CF 2 H • and CH 2 CF 3 • radical species with a range of heteroarenes (Scheme 51). Similarly, the Zhang and Fang group recently reported the use of sodium difluoromethanesulfinate for the electrochemically induced difluoromethylation of quinoline and isoquinoline N ‐oxides [134] …”
Section: Perfluoroalkylation Of (Hetero)arenesmentioning
confidence: 98%
“…Six-membered N -heteroarenes are important substructures found in numerous bioactive compounds. In most cases, functionality is incorporated into the pyridine ring system through pyridine ring synthesis or from commercial sources, which can limit access to more complex scaffolds. C–H alkylation of heteroarenes, on the other hand, offers a direct method to prepare a diverse range of functionality from easily accessible starting materials. Photocatalytic and electrochemical Minisci-like reactions that involve the addition of alkyl radicals to heteroarenes have allowed for the formation of new C–C bonds and the direct incorporation of diverse functionality. The use, however, of external terminal oxidants, sacrificial electron donors, and expensive photocatalysts limits, to some extent, the overall utility.…”
mentioning
confidence: 99%
“…CV experiments showed that the C�C double bond in the product was formed via an addition−oxidation−elimination procedure. At the beginning, sulfonyl hydrazide (114) was activated at the anode by an iodide cation and yielded a radical species (117) at the anode; in this phase, the sulfonyl iodide (115) was proven to be a key intermediate. The radical (117) also could be gained from the sulfonyl iodide (115) via a sulfonyl anion intermediate (116).…”
Section: Sulfonylation Of Alkenes and Alkynesmentioning
confidence: 99%